Crossing intersectoral boundaries to reach out to vulnerable populations with chronic conditions in five European regions - Rosete, Arturo Alvarez; Pisano-González, Marta M; Boone, An LD; Vazquez-Alvarez, Raquel; Peñacoba-Maestre, Delia; Valsecchi, Verushka; Pers, Yves-Marie; Zora, Sabrina; Pilotto, Alberto; Tan, Siok-Swan; Raat, Hein; Baker, Graham; et al. (Archives of Community Medicine and Public Health, 2021)
Introduction: Vulnerable people with chronic conditions should be a priority of policy and interventions. Very often, however, they are hard-to-reach and reluctant “to come to see us”. This paper describes the intersectoral alliances used in the EU funded project EFFICHRONIC to identify and enrol hard-to-reach vulnerable populations with chronic conditions to participate in a self-care programme. Methods: The recruitment approach combined population-based and individual strategies. Vulnerability maps based on specific deprivation indices were developed to prioritize the intervention in those areas with higher vulnerability. Within those areas, potential participants were individually recruited following a variety of recruitment strategies. Results: To reach the vulnerable population, alliances with local and regional authorities, health services, social care organizations and civil society were generated across the EFFICHRONIC sites. As a result of this collaborative effort, a total number of 2.951 vulnerable participants distributed over the 5 European countries have been engaged. Discussion: Forging cross-sectoral alliances has been both enriching and challenging. Our key learnings from this experience include: create a persuasive vision; identify the right agents in the territory, the key people in the organisations and the influential leaders within the community; keep continuous liaison and communications, and ensure effective leadership. Conclusion: Our learnings can contribute to future improvements for policy and practice.